2015
DOI: 10.1007/s00198-015-3034-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of differing resistance training modes on the preservation of bone mineral density in postmenopausal women: a meta-analysis

Abstract: Combined resistance exercise protocols appear effective in preserving femoral neck and lumbar spine BMD in postmenopausal women, whereas resistance-alone protocols only produced a nonsignificant positive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 68 publications
7
113
0
8
Order By: Relevance
“…If mechanical unloading contributes to bone loss, possibly and at least partially via changes in sclerostin secretion, then weight-bearing exercises (which includes resistance training and high impact weight bearing exercises such as running, jogging, skipping and dancing) might be expected to overcome this effect. Meta-analyses conclusively report that weight bearing exercises -notably resistance training combined with high impact weight bearing exercise -significantly preserve BMD compared to other forms of exercise, including jogging mixed with walking or stair climbing or agility exercises, in pre-or post-menopausal women [100][101][102]. In one of these meta-analyses, resistance training combined with high-impact weight bearing exercises was found to be better at enhancing BMD in postmenopausal women than resistance training alone [101].…”
Section: Possible Mechanisms Of Bone Loss Induced By Obesity Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…If mechanical unloading contributes to bone loss, possibly and at least partially via changes in sclerostin secretion, then weight-bearing exercises (which includes resistance training and high impact weight bearing exercises such as running, jogging, skipping and dancing) might be expected to overcome this effect. Meta-analyses conclusively report that weight bearing exercises -notably resistance training combined with high impact weight bearing exercise -significantly preserve BMD compared to other forms of exercise, including jogging mixed with walking or stair climbing or agility exercises, in pre-or post-menopausal women [100][101][102]. In one of these meta-analyses, resistance training combined with high-impact weight bearing exercises was found to be better at enhancing BMD in postmenopausal women than resistance training alone [101].…”
Section: Possible Mechanisms Of Bone Loss Induced By Obesity Treatmentsmentioning
confidence: 99%
“…Meta-analyses conclusively report that weight bearing exercises -notably resistance training combined with high impact weight bearing exercise -significantly preserve BMD compared to other forms of exercise, including jogging mixed with walking or stair climbing or agility exercises, in pre-or post-menopausal women [100][101][102]. In one of these meta-analyses, resistance training combined with high-impact weight bearing exercises was found to be better at enhancing BMD in postmenopausal women than resistance training alone [101]. Moreover exercise, particularly weight-bearing exercise, has been shown to reduce BMD losses during dietary restriction [93,103].…”
Section: Possible Mechanisms Of Bone Loss Induced By Obesity Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined resistance training protocols were defined as the combination of resistance training and high-impact or weight-bearing exercise. The results suggested that the combined resistance training protocols were effective in improving bone mineral density at the femoral neck and lumbar spine [21].…”
Section: Evidences About the Effect Of Physical Exercises On Bone Massmentioning
confidence: 92%
“…Hezur-osasunean onura nabarmenenak erresistentzia-entrenamenduetan jauziak eta saltoak pixkanaka modu progresiboan gehitzen joan heinean antzeman dira [40]. Modu honetan, hezurrean zeharka eragiten duten giharren indarra eta funtzionaltasuna lantzearekin batera, hezur-osasuna hobetu egiten da [41].…”
Section: Talkadun Erresistentzia-ariketakunclassified